FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIK DI BEI (Students' Journal of Accounting and Banking, 2012)
The reseach is in an examinitam which examine and analyze the influence of size of the company, business risk, active growth, and profitability towards the capital structure in go public manufacture company in Indonesia Stock Exchange in 2007-2009.The Population of the research is a manufacture company which is joined In Indonesia Stock Exchange since 2007 until 2009. Meanwhile, the sample of the research is a go public manufacture company which is joined in Indonesia Stock Exchange from 2007 to 2009 by taking’’ Purposive Sampling’’ sample.The Result of the research shows that the hypothesis examination result shows that: (a). The size of the company has positive significant influence towards the capital structure of go public manufacture company in 2007-2009. (b). The business risk doesn’t have influence towards the capital structure of go public manufacture company in 2007-2009. (c) The active growth has positive significant influence towards the capital structure of go public manufacture company in 2007-2009. (d) Profitability has negative significant influence towards the capital structure of go public manufacture company in 2007-2009. The size of company, business risk, active growth, and profitability simultantly has an influence towards the capital structure variable.Keywords: The size of the company, business risk, active growth, and capital structure profitability.